Dutch Minister for Foreign Affairs Van der Stoel (right) recieves his French collegue on Ypenburg airport. Text on the back
Dutch Minister for Foreign Affairs Van der Stoel (right) recieves his French collegue on Ypenburg airport. Text on the back.